Larval redescription of Microstigma maculatum Hagen in Selys, 1860 (Odonata: Pseudostigmatidae) from Manaus, Amazonas, Brazil - Neiss, Ulisses Gaspar; Lencioni, Frederico A.A.; Hamada, Neusa; Ferreira-Keppler, Ruth Leila Menezes (Zootaxa, 2008)
The last-instar larva of Microstigma maculatum Hagen in Selys, 1860 is redescribed and illustrated based on a reared larva collected in a water-filled hole of a fallen tree trunk within an urban forest fragment in Manaus, Amazonas, Brazil. Copyright © 2008 - Magnolia Press.
Keywords: Hexapoda; Microstigma Maculatum; Odonata; Pseudostigmatidae; Zygoptera